The effect of shooting a stationary ball and a moving ball to wear the shooting accuracy of soccer academy - Habid Wipa Rayhananda; Mohamad Annas (Sriwijaya Journal of Sport, 2025)
Research Problems: Many young soccer players struggle to maintain consistent shooting accuracy when transitioning between shooting a stationary ball and a moving ball during gameplay. This study examines the impact of the ball's condition—stationary versus moving—on the shooting accuracy of 14–to 15-year-old soccer players. Research Objectives: This study aims to determine the effect of stationary ball and moving ball shooting training on improving shooting accuracy in soccer. Methods: The research used a two-group pretest-posttest design with a total sample of 26 participants, divided evenly into two groups of 13. The first group underwent stationary ball shooting training, while the second group participated in moving ball shooting training. A shooting accuracy test was used as the research instrument to measure performance before and after the intervention. Results: The pretest results showed that the stationary ball group had an average value of 63.08, which increased to 77.69 in the posttest. Similarly, the moving ball group increased from an average of 60.00 to 74.62. An increase of 14.62 points in both groups. Data analysis involved the Shapiro-Wilk normality test and Levene’s homogeneity test, confirming that the data were normally distributed and homogeneous (p > 0.05). The Paired Samples t-test showed a significant difference between the pretest and posttest values in both groups (p = 0.000), indicating that the training given was effective in improving the accuracy of shots on goal. However, based on the Independent Samples Test, there was no significant difference between the two groups (p = 0.454), although the average posttest score of the stationary ball group was slightly higher. Conclusion: Thus, stationary ball and moving ball shooting exercises are equally effective in improving shooting accuracy. These results support the implementation of both training methods in basic soccer coaching programs to enhance players' shooting precision. Future research should investigate the long-term effects of both training types across various age groups and skill levels to enhance generalizability and provide a broader understanding of optimal training strategies.